Preparation of Supported Palladium Catalyst for Selective Hydrogenation of Phenylacetylene by Double Impregnation Method - Li, Changyou; Cheng, Zhenfeng (Asian Journal of Chemistry, 2012)
In this paper, Pd-Pb/CaCO3 catalysts for selective hydrogenation of phenylacetylene were prepared by double impregnation method, which was compared with those prepared by conventional impregnation method, and the results showed that the addition of a certain amount of EDTA could improve the catalytic selectivity significantly. When impregnation ratio was 10 g CaCO3/10 mL EDTA, absorption rate of hydrogen was moderate and selectivity was highest (95.9 %). This was possible due to the fact that the addition of EDTA leads to a balanced increase of terrace type surface.